ANALISIS BIAYA PRODUKSI PT. TJIWI KIMIA Tbk - Indri Damayanti; Tatyana Tatyana (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2020)
Management always tries to make the output value higher than the value of the input sacrificed to produce that output, so that organizational activities can generate profits (for profit-motivated companies) or residual results (for companies that are not profit-motivated). With these profits or the remaining results of operations, the company will have the ability to develop and still be able to maintain its existence as a system in the future. Thus, to ensure that a business activity produces an output value that is higher than the input value, a tool is needed to measure the value of the input sacrificed to produce output. In providing services to PT. Tjiwi Kimia Tbk. There are two types of costs such as production costs and non-production costs. Production costs are costs incurred in processing raw materials into products or services, while non-production costs are costs incurred for non-production activities such as marketing costs and general and administrative activities in the production process at PT. Tjiwi Kimia Tbk. it has a cost classification that has been structured to provide its services